On atomic mechanisms governing the oxidation of Bi2Te3. (9th November 2017) - Music, Denis; Chang, Keke; Schmidt, Paul; Braun, Felix N; Heller, Martin; Hermsen, Steffen; Pöllmann, Peter J; Schulzendorff, Till; Wagner, Cedric
Abstract: Oxidation of Bi2 Te3 (space group R 3 ̄ m ) has been investigated using experimental and theoretical means. Based on calorimetry, x-ray photoelectron spectroscopy and thermodynamic modelling, Bi2 Te3 is at equilibrium with Bi2 O3 and TeO2, whereby the most stable compound is Bi2 Te3, followed by Bi2 O3 . The reactivity of Bi towards oxygen is expected to be higher than that of Te. This notion is supported by density functional theory. The strongest bond is formed between Bi and Te, followed by Bi–O. This gives rise to unanticipated atomic processes. Dissociatively adsorbed oxygen diffuses through Bi and Te basal planes of Bi2 Te3 (0 0 0 1) and preferably interacts with Bi. The Te termination considerably retards this process. These findings may clarify conflicting literature data. Any basal plane off-cut or Bi terminations trigger oxidation, but a perfect basal cleavage, where only Te terminations are exposed to air, may be stable for a longer period of time. These results are of relevance for applications in which surfaces are of key importance, such as nanostructured Bi2 Te3 thermoelectric devices.